Relações entre o desempenho lingüístico-textual e o conhecimento gramatical explícito: estudo aplicado a jornalistas do jornal Estado de Minas - Fernanda Teixeira da Costa Mendes (2006)
This dissertation has the following hypothesis as its guiding principle: to investigate to what extent the knowledge of explicit traditional grammar contributes to the writing practice of the journalists of "Estado de Minas", the most widely distributed newspaper in the State of Minas Gerais. The intention was to find out what degree of knowledge about concepts, classifications and terminology mostly taught in Portuguese classes these professionals possess. One of the purposes of this research work is to arouse reflection on the part of Portuguese Language teachers about methods used in teaching the standard written variety of the language and to suggest that they begin to use strategies such as "retextualization" (Marcuschi, 2003) in teaching standard writing. In order to back up the development of the research, a questionnaire was developed which should allow us to draw a profile of the journalists regarding the conception of traditional grammar that they have. And also to find out whether the study of traditional grammar has provided them with linguistic elements to write in the standard variety. Two paragraphs of a text written by one of the journalists of the "Gerais" section were used to develop traditional exercises, according to models proposed in normative grammars and a great number of textbooks. The analysis of the questionnaire has revealed that the power and authority of traditional grammar are quite relevant. An unsatisfactory performance in doing grammar exercises has shown that being able to write in the standard written variety is very different from knowing traditional grammar, i.e., knowing about concepts, identifying parts of clauses, classifying them according to the terminology proposed in normative compendia are not indispensable conditions for a good performance in writing. This means that it is perfectly possible to learn standard writing without aid from traditional grammar.